Evaluation of the modified carbapenem inactivation method for the detection of carbapenemase-producing Enterobacteriaceae. Issue 4 (April 2018) - Kuchibiro, Tomokazu; Komatsu, Masaru; Yamasaki, Katsutoshi; Nakamura, Tatsuya; Nishio, Hisaaki; Nishi, Isao; Kimura, Keigo; Niki, Makoto; Ono, Tamotsu; Sueyoshi, Noriyuki; Kita, Machiko; Kida, Kaneyuki; et al.
Abstract: Carbapenemase-producing Enterobacteriaceae (CPE) are increasing worldwide. Rapid and accurate detection of CPE is necessary for appropriate antimicrobial treatment and hospital infection control. However, CPE contains some strains that are difficult to detect depending on genotype and MIC value of carbapenem, and a detection method has not been established. The recently reported modified carbapenem inactivation method (mCIM) has been developed in CLSI M100-S27 as a phenotypic technique for detecting carbapenemase activity. In the present study, we examined mCIM as a new CPE detection method using 207 Enterobacteriaceae isolates in comparison with the three existing screening methods of modified Hodge test, Carba NP test and carbapenem inactivation method and evaluated its performance. Consequently, both the sensitivity and specificity of mCIM were 100%, indicating better results than the conventional screening methods. The mCIM is a useful tool for microbiology laboratories due to its simplicity, clear criteria, cost-effectiveness and availability at any laboratory.